2010
DOI: 10.1128/jcm.01869-09
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genotypic Diversity ofMycobacterium aviumSubspecies from Human and Animal Origins by Mycobacterial Interspersed Repetitive-Unit-Variable-Number Tandem-Repeat and IS1311Restriction Fragment Length Polymorphism Typing Methods

Abstract: Members of the Mycobacterium avium complex (MAC) are ubiquitous bacteria that can be found in water, food, and other environmental samples and are considered opportunistic pathogens for numerous animal species, mainly birds and pigs, as well as for humans. We have recently demonstrated the usefulness of a PCR-based mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) typing for the molecular characterization of M. avium subsp. paratuberculosis and M. avium strains exclusively is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
82
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 48 publications
6
82
2
1
Order By: Relevance
“…Studies on the use of VNTR analysis for M. intracellulare isolates were reported from Japan and France in 2009 and 2010 (11,13), respectively, and from the United States in 2013 (12). Similar studies on the use of VNTR analysis for M. avium isolates have also been reported, but none of those studies evaluated isolates from the United States (9,15,18). Here we describe the use of M. avium VNTR analysis for comparison of environmental water and respiratory disease isolates from the United States and utilization of the composite data to create a database of isolates.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Studies on the use of VNTR analysis for M. intracellulare isolates were reported from Japan and France in 2009 and 2010 (11,13), respectively, and from the United States in 2013 (12). Similar studies on the use of VNTR analysis for M. avium isolates have also been reported, but none of those studies evaluated isolates from the United States (9,15,18). Here we describe the use of M. avium VNTR analysis for comparison of environmental water and respiratory disease isolates from the United States and utilization of the composite data to create a database of isolates.…”
mentioning
confidence: 71%
“…Such studies include the use of mycobacterial interspersed repetitive unit (MIRU) loci (8) and M. avium tandem-repeat (MATR) loci (some of which recognize the same tandem repeat) (9). VNTR analysis has been used for strain comparisons and population studies of other species of mycobacteria, including M. intracellulare, Mycobacterium ulcerans, and Mycobacterium tuberculosis (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Studies on the use of VNTR analysis for M. intracellulare isolates were reported from Japan and France in 2009 and 2010 (11,13), respectively, and from the United States in 2013 (12).…”
mentioning
confidence: 99%
“…In summary, separation of M. intracellulare into distinct groups can now be done worldwide as has been done for multiple other genera and species, including M. tuberculosis (8)(9)(10)(11)(12)(13)(14)(15). This characterization should be done to allow us to begin to understand the significance and virulence of different groups and species in the large family currently known as M. avium complex.…”
Section: Discussionmentioning
confidence: 99%
“…Variable-number tandem (i.e., consecutive) repeats (VNTR) of the minisatellite class (10 to 100 bp) were identified. VNTR typing has been used for strain comparison and population studies of other species of mycobacteria, including Mycobacterium ulcerans, Mycobacterium avium, and Mycobacterium tuberculosis (8)(9)(10)(11)(12)(13)(14)(15). Subsequently, studies of the use of VNTR for M. intracellulare isolates were reported in 2009 and 2010 from Japan (16) and (Bordeaux) France (17), and the candidate markers were described as mycobacterial interspersed repetitive unit-variable-number tandem repeats (MIRU-VNTR) (17).…”
mentioning
confidence: 99%
“…Although the dogs surveyed did not present symptoms of MAC infection, some clinical signs such as anorexia, fever, diarrhea, lymphadenopathy, or lameness have been described depending on the dissemination degree and/or organ involvement (4,5,17,18). Previous studies also indicated that breeds such as miniature schnauzers and basset hounds are more predisposed to mycobacterial infection (5,10,17,19), although no differences were observed among Portuguese hunting breeds and crossbreeds. Moreover, immunocompromised animals are thought to be at greatest risk (5).…”
mentioning
confidence: 90%